Diversity of organic amendments increases soil functions and plant growth - Huiying Li; Anika Lehmann; Rebecca Rongstock; Yaqi Xu; Edda Kunze; Peter Meidl; Matthias C. Rillig (Plants, People, Planet)
Societal Impact Statement Management practices, for example, in an agricultural context, are often tested in isolation or in pairwise interaction, but rarely using a higher number of jointly applied practices. In a proof‐of‐concept study, we test the effects of combining up to five management practices. Effects seen on soil and plant performance suggest that it may be worth to systematically and broadly examine the effects of higher order management combinations.